Oxidation, Glycation, and Carbamylation of Salivary Biomolecules in Healthy Children, Adults, and the Elderly: Can Saliva Be Used in the Assessment of Aging? - Maciejczyk M; Nesterowicz M; Szulimowska J; Zalewska A (Dove Medical Press, 2022)
Mateusz Maciejczyk,1 Miłosz Nesterowicz,2 Julita Szulimowska,3 Anna Zalewska3 1Department of Hygiene, Epidemiology and Ergonomics, Medical University of Bialystok, Bialystok, Poland; 2Students Scientific Club "Biochemistry of Civilization Diseases" at the Department of Hygiene, Epidemiology, and Ergonomics, Medical University of Bialystok, Bialystok, Poland; 3Department of Conservative Dentistry, Medical University of Bialystok, Bialystok, PolandCorrespondence: Mateusz Maciejczyk, Department of Hygiene, Epidemiology and Ergonomics, Medical University of Bialystok, 2c Mickiewicza Street, Bialystok, 15-233, Poland, Email mat.maciejczyk@gmail.comBackground: Aging is inextricably linked to oxidative stress, inflammation, and posttranslational protein modifications. However, no studies evaluate oxidation, glycation, and carbamylation of salivary biomolecules as biomarkers of aging. Saliva collection is non-invasive, painless, and inexpensive, which are advantages over other biofluids.Methods: The study enrolled 180 healthy subjects divided into six groups according to age: 6- 13, 14- 19, 20- 39, 40- 59, 60- 79, and 80- 100 years. The number of individuals was determined a priori based on our previous experiment (power of the test = 0.8; α = 0.05). Non-stimulated saliva and plasma were collected from participants, in which biomarkers of aging were determined by colorimetric, fluorometric, and ELISA methods.Results: The study have demonstrated that modifications of salivary proteins increase with age, as manifested by decreased total thiol levels and increased carbonyl groups, glycation (Nϵ-(carboxymethyl) lysine, advanced glycation end products (AGE)) and carbamylation (carbamyl-lysine) protein products in the saliva of old individuals. Oxidative modifications of lipids (4-hydroxynonenal) and nucleic acids (8-hydroxy-2'-deoxyguanosine (8-OHdG)) also increase with age. Salivary redox biomarkers correlate poorly with their plasma levels; however, salivary AGE and 8-OHdG generally reflect their blood concentrations. In the multivariate regression model, they are a predictor of aging and, in the receiver operating characteristic (ROC) analysis, significantly differentiate children and adolescents (under 15 years old) from the working-age population (15- 64 years) and the older people (65 years and older).Conclusion: Salivary AGE and 8-OHdG have the most excellent diagnostic utility in assessing the aging process. Saliva can be used to evaluate the aging of the body.Graphical Abstract: Keywords: saliva, aging, protein oxidation, protein glycation, protein carbamylation, DNA oxidation